Inquiry as a Part of Educational Reality in Technical Education - Mária Kožuchová; Silvia Barnová; Ján Stebila (Emerging Science Journal, 2022)
In the proposed study, the authors focus on the situation in the field of technical education in Slovak primary schools and present the results of an original research study focused on the application of an inquiry-based approach. The main goal of the investigation was to compare the efficiency of using inquiry-based activities in teaching selected topics (Electromagnetism and Electronics) with the efficiency of traditional teaching methods where students follow their teacher’s instructions. In the presented research study, carried out in four primary schools, the methods of pedagogical experiment and didactic tests examining students’ knowledge on the three levels of Niemierko’s taxonomy were used. The authors of the study present their findings regarding the impact of inquiry-based teaching on 6th grade students’ knowledge, activity, and motivation. Based on the obtained results, it can be assumed that inquiry-based teaching can lead to better knowledge acquisition, increased student activity, and a higher motivation to learn compared with applying traditional methods of teaching. The results of the t-testconfirmed the significance of differences between the experimental group’s and the control group’s performance in all three observed fields. The authors believe that the presented findings can contribute to improving the quality of the educational process not only in technical education but in other fields of didactics as well. Doi: 10.28991/ESJ-2022-SIED-016 Full Text: PDF